2009
DOI: 10.4315/0362-028x-72.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli O157:H7 in Single-Strength Lemon and Lime Juices

Abstract: Survival of a five-strain mixture of stationary phase (nonadapted) and acid-adapted Escherichia coli O157:H7 in single-strength lemon and lime juices was evaluated at room temperature (22 degrees C). The juices were reconstituted from concentrates that contained no preservatives and intrinsic pH values of 2.5 to 2.6 and titratable acidities of 4.51 to 4.53% (wt/vol, citric acid). A greater than 5-log reduction of stationary-phase cells was achieved in both lemon and lime juices after 72 h of incubation. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…Our results are in agreement with recently published data showing that certain non-0157 STEC strains may react similarly to E. coli 0157:H7 under food-relevant conditions, including temperature, pH, aw, and salt (14,28,32). For example, Enache et al (15) compared the thermal resistance parameters (/7-values) in apple juice of six non-0157 STEC serotypes with those of 0157 (15).…”
Section: )supporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in agreement with recently published data showing that certain non-0157 STEC strains may react similarly to E. coli 0157:H7 under food-relevant conditions, including temperature, pH, aw, and salt (14,28,32). For example, Enache et al (15) compared the thermal resistance parameters (/7-values) in apple juice of six non-0157 STEC serotypes with those of 0157 (15).…”
Section: )supporting
confidence: 92%
“…In the current study, additional lethality was observed when pepperoni chubs were stored at 12.8°C for 7 and 14 days (without additional drying). The additional bacterial destruction may be attributed to prolonged exposure of injured cells to the low pH-low moisture conditions and to higher than refrigeration temper ature; it is well recognized that bacterial pathogens survive better in products stored at refrigeration temperature than at ambient temperature (20 to 30°C) (14,28).…”
Section: )mentioning
confidence: 99%
“…It should be noted that of all seven serotypes, only E. coli O157:H7 (strain N-4173) had significantly higher (P , 0.05) D-values for stationary-phase cells for all tested temperatures in apple juice at pH 3.7. The E. coli O157:H7 strains used for comparison were chosen because they have been implicated in either apple cider or apple juice outbreaks and they have been used in previous heat resistance or survival studies in our laboratories (13)(14)(15)29).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that pH-dependent acid resistance provided E. coli O157:H7 with cross-protection against heat treatments at elevated pH values but no cross-protection when the pH of the heating medium was ,4.0. Several studies involving acid-adapted pathogens in heated juice products (6, 14) as well as products stored at refrigeration (220 to 4uC) or room temperatures (22uC), such as ground beef, apple cider, cranberry juice concentrates, and lemon and lime juices (13,15,20,38) showed that acid adaptation did not offer enhanced protection during exposure to a subsequent environmental stress in an actual food product.…”
Section: Discussionmentioning
confidence: 99%
“…While the ability of E. coli O157:H7 to survive in acidic conditions has been extensively studied (10,18,22), there are relatively few studies regarding the survival of other pathogenic STEC serotypes under the same conditions. Moreover, the published reports on survival abilities of E. coli O157 versus non-O157 in acidic conditions do not always agree.…”
mentioning
confidence: 99%